Análise do controle autonômico cardíaco e do metabolismo muscular durante o exercício descontínuo dinâmico e resistido em homens jovens e idosos - Simões, Rodrigo Polaquini (Universidade Federal de São Carlos, 2012)
The thesis consisted of three studies described below. Study I, which aimed to investigate the effect of aging on kinetic responses of heart rate (HR) and oxygen consumption (VO2) during rest-exercise (ontransient) and exercise-recovery transitions (off-transient), and to investigate the influence of exercise intensity (mild and moderate) on the kinetic parameters of these variables. 28 apparently healthy men were evaluated, and 14 constituted the young group (YG) and 14 the elderly group (EG). The evaluation consisted of applying an incremental exercise testing of ramp protocol on cycle-ergometer (IET-R) to determine the maximum power (MP) and discontinuous exercise test on a cycle ergometer (DET-C), which started with an initial power load of 10% of MP with subsequent increase of 10% until exhaustion. Were recorded ventilatory and metabolic variables, the HR and blood lactate at rest and during exercise. The lactate threshold (LT) was closed between the groups (approximately 30% of MP). The EG showed higher values of the kinetic responses, both on and off transitions of HR and VO2 (p<0.05), and the values were higher in moderate compared to mild in YG (p<0.05). We conclude that the elderly have slower kinetic responses of HR and VO2 in relation to young and that at moderate intensity; the kinetic responses were slower in relation to mild intensity in young. Following, the study II aimed to investigate the behavior of the heart rate variability (HRV) responses during a discontinuous resistance exercise (RE) protocol and check whether they agree with the blood lactate responses in the determination of anaerobic threshold (AT) in apparently healthy young and elderly. For this proposal, in the same volunteers in the study I, was applied the test of one repetition maximum (1RM) on the leg press 45º and the discontinuous exercise test on the leg press 45 (DET-L), initiated in 10% of 1RM subsequent increments of 10% until exhaustion, and the HR and blood lactate were obtained at rest and during exercise. The AT was determined at approximately 30% of 1RM in both groups and both methods of analysis (blood lactate and HRV), the HRV index decreased with increasing load and stabilized from the load corresponding to AT in both groups, additionally the blood lactate remained practically stable until the load of AT, and increased significantly after this intensity. The EG had lower HRV values in lower loads of AT, and lower values of HR and blood lactate in loads above of AT in relation to the YG. We conclude that the HRV responses to determine the AT are according to blood lactate, and that the increase in load during the discontinuous RE promoted gradual vagal withdrawal followed by sympathetic activation in both young and the elderly, however, these responses are attenuated with the aging process. Finally, the study III, aimed to determine the AT during discontinuous dynamic and resistance exercise protocol by analyzing blood lactate and HRV in healthy older adults, comparing the cardiovascular, metabolic and autonomic variables between these two exercise modalities. We evaluated the elderly group of individuals during the tests: IET-R, DET-C, 1RM and DET-L. The AT within about 30% of maximum intensity in both the DET-C and DET-L by both methods (blood lactate and HRV). There were no differences in HRV variables between the modalities of exercise and a significant increase in systolic blood pressure and blood lactate after AT load in the DET-L. We conclude that HRV was effective in determining the AT and that the parasympathetic modulation responses were similar between dynamic and resistance exercise.
Keywords: Fisiologia do exercício físico - frequência cardíaca; Envelhecimento; Exercício resistido; Exercício dinâmico; Limiar de anaerobiose; Cinética; Modulação autonômica cardíaca; Aging; Resistance exercise; Dynamic exercise; Cardiac autonomic modulation; Anaerobic threshold; Kinetic; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL